Mind Mapping of Consumers : A Study to Explore the Role of Religion - Saini, Swati; Kumar, Rajiv (Indian Journal of Marketing, 2023)
This paper aimed to explore the religious practices adopted by Hindu consumers and reveal the significant decisions affected by following these practices. With culture, decisions differ, so an effort was made to understand why these religious practices were adopted. It was empirical research for which an open-ended semi-structured questionnaire was used. Hindu consumers filled out the questionnaire in a face-to-face interaction. Responses from 30 individuals were collected in descriptive form. NVivo 12 software was used to analyze the data. The word cloud and themes indicated that many religious practices were followed during festivals and other religious events. Consumers follow religious practices at festivals, weekdays, and other events. We observed that major decisions affected by adopting these religious practices were consumption, purchasing, services, and color preference. Consumers’ religious beliefs influenced all decisions. They followed religious practices due to their belief in God, religion, family teachings, myths, superstitions, health concerns, and family pressure. This study could be generalized by quantifying it in future research. The study also provided insights to companies about the significant role of religious practices in consumer decision-making. Companies can understand the religious practices followed and create a better consumer experience. The study was limited to Indian Hindu consumers, so an analysis of other religions is needed. The study is unique, providing a new perspective on understanding Hindu consumers.